Build an early foundation for algebra success. (March 2016) - Knuth, Eric; Stephens, Ana; Blanton, Maria; Gardiner, Angela
Research tells us that success in algebra is a factor in many other important student outcomes. Emerging research also suggests that students who are started on an algebra curriculum in the earlier grades may have greater success in the subject in secondary school. What's needed is a consistent, algebra-infused mathematics curriculum all throughout the earlier grades. The authors outline three foundational principles for students to learn in the early grades, which can help them with the algebra they encounter in secondary school.